Application of Mysterious Boxes and Cards Game Media (KOKAMI) in Learning Mandarin Sentence Writing Skills for Grade VII Students of SMP Frather Makassar - Muhamad Rama Muhyinur Syarifuddin; Ambo Dalle; Arini Junaeny (Universitas Negeri Semarang, 2023)
Through the use of the Mysterious Boxes and Cards Game Media (KOKAMI), this study seeks to enhance the class VII students of SMP Frather Makassar's ability to write Mandarin sentences. Based on the findings of the observations, 31 students from class VII A of SMP Frather Makassar were chosen as the research subjects. This study is an example of a classroom action research that collects data in two ways: quantitative data from writing skill tests administered in cycles I and II and qualitative data utilizing the guidelines on observation sheets. The study's findings demonstrate that the use of the KOKAMI game medium may be used to teach writing skills, with a learning completeness score of 87% in cycle I and 94% in cycle II. These findings suggest that class VII students at SMP Frather Makassar may write Chinese phrases more effectively by using the KOKAMI gaming medium.